4E analyses and multi-objective optimization of cascade refrigeration cycles with heat recovery system. (1st October 2020) - Golbaten Mofrad, Kamyar; Zandi, Sina; Salehi, Gholamreza; Khoshgoftar Manesh, Mohammad Hasan
Highlights: Cascade refrigeration and heat recovery cascade refrigeration cycles are compared. The coefficient of performance and exergy efficiency of the heat recovery cascade refrigeration cycle are more. Exergoeconomic and exergoenvironmental analyses of the heat recovery cascade refrigeration cycle are carried out. Advanced exergy and exergoeconomic analyses based on Engineering Approach are conducted. Multi-objective optimization of heat recovery cascade refrigeration is performed. Abstract: In this paper, thermodynamic simulation and analyses of cascade refrigeration and heat recovery cascade refrigeration cycles are investigated. Due to the high heat dissipation in the gas cooler in the cascade refrigeration cycle, the heat recovery cascade refrigeration cycle uses this heat to launch a Rankine cycle. R744 refrigerant for the high-temperature circuit and R744A refrigerant for the low-temperature circuit are used. Energy, exergy analyses for these cycles have been performed. Due to the better performance of the heat recovery cascade refrigeration system, advanced exergy, exergoeconomic, and exergoenvironmental, analyses have been performed for this cycle with Engineering Approach. In this regard, computer code was developed to compute these analyses. Multi-objective optimization of the cycle by the genetic algorithm has been performed with the objective functions of exergy efficiency and total product cost as well as the coefficient of performance and product environmental impact. Exergoeconomic analysis demonstrates that the product cost rate for the cycle is 3.4 $. h -1 . Based on exergoenvironmental analysis, the compressor1 has the highest environmental impact. The optimization results reveal that using the heat recovery cascade refrigeration cycle leads to an increasing 7.6% coefficient of performance and 12.5% exergy efficiency.